Interviews with children and adolescents with epilepsy or asthma about the situation of their healthy siblings. (29th January 2023) - Charisius, Mathilda; Jeschke, Sarah; Lange, Sarah; Bertsche, Thilo; Ballmann, Manfred; Neininger, Martina P.; Bertsche, Astrid
Abstract: Aim: Chronic conditions can influence the situation of healthy siblings of affected children. We investigated the opinion of the affected child about the situation of their healthy sibling and the sibling relationship. Methods: We performed a semi‐structured interview with epilepsy or asthma patients aged 6–18 years and asked them to draw a picture: "Epilepsy/Asthma, my siblings and me." Results: Of the 58 children with epilepsy, 67%, and of the 40 children with asthma, 60% thought that their siblings were worried about the condition. Among other aspects, they addressed helplessness during a seizure. Of the children with epilepsy, 83% and of those with asthma, 95% assumed that their siblings were not disadvantaged because of the participant's condition. Of the patients with epilepsy, 91% and of those with asthma, 93% thought that the sibling relationship would not be different without the condition. Of the participants with epilepsy, 86% and of those with asthma, 93% drew a picture; 30% with epilepsy and 14% with asthma visualised an interaction with their siblings in context of a seizure or episode of dyspnoea. Conclusion: According to the affected children, the condition worries their siblings but does not affect the siblings' lives or the sibling relationship.